Evaluating the accuracy of the AedesTech Mobile App (ATA): a mobile application for assessing population surveillance of Aedes to aid in combatting dengue - Fatin Nabila; Lim, Chee Hwa; Mustafa Man; Ahmad Mohiddin Mohd Ngesom; Wan Fatma Zuharah (Penerbit Universiti Kebangsaan Malaysia, 2025)
Ovitrap can be used for monitoring Aedes mosquitoes and some of them were built for controlling the Aedes population such as the AedesTech Mosquito Home (AMHS) trap which utilizes pyriproxyfen. While ovitraps play a crucial role in monitoring Aedes mosquito transmission, manual counting of mosquito eggs within these traps proves labour-intensive and error prone. To address this challenge, the AedesTech Mobile App (ATA) was developed and continues to iterate, aiming to calculate the precise number of eggs attached to OviTo linen, an oviposition strip in AMHS, where gravid mosquitoes lay eggs. This mobile application modernizes the process by capturing OviTo linen images and automatically counting Aedes mosquito eggs through image analysis, securely storing data in the cloud. The app further enhances efficiency by facilitating precise ovitrap location tracking via QR codes. Research focuses on evaluating ATA's precision based on 1358 pieces of OviTo linen in assessing mosquito populations in the multilevel Asoka Apartment in Penang. A comparison between ATA version v0.9.3 and manual counting methods reveals a consistent 3.53% accuracy across all collected OviTo linen. There was less observable improvement in ATA accuracy over three consecutive periods. The study underscores the necessity for enhancements in ATA version v0.9.3 to address limitations and achieve more accurate counts in mosquito population assessments.